Effects of exogenous metallothionein on acute cadmium toxicity in rats - Kara, H; Karatas, F; Canatan, H; Servi, K (Springernature, 2005)
The present study was carried out to evaluate the effect of exogenously administered metallothionein (MT) to rats exposed to high cadmium levels. A total of 72 rats were used in the study. The animals were divided into three groups: controls, Cd administered, and Cd+MT. Cadmium was administered by subcutaneous injection of cadmium(II) chloride at a dose of 3.5 mg/kg for 7 d. In addition to CdCl2, 30 mu mol/kg MT was administered to the second group of rats (group II). Control rats received 0.5 mL physiologic serum via subcutaneous injection. Eight rats from each group were sacrificed on the 1st, 3rd, 5th, and 7th day after administration of the compounds. Liver, kidney, and blood samples were harvested. Levels of malonclialdehyde (MDA), glutathione peroxidase (GSH-Px), serum ALT, AST, BUN, ALP, creatinine, and urea were measured. MDA levels in group I were observed to increase starting from d 1 compared to group II (p < 0.05). Although MDA levels in group II were higher than controls (p < 0.05), they were lower, especially in liver and blood, compared to group II. Erythrocyte GSH-Px activity levels were determined to decrease starting from d I in both groups (p < 0.05). Decreases in GSH-Px activity levels in group II were less than group I. Serum creatinine levels in both groups were increased significantly compared to controls (p < 0.05); the increase in group I was higher than group II. Serum ALT, AST, and ALP levels in group I increased to very high levels compared to controls, whereas increases in group II were at moderate levels (p < 0.05). Although serum BUN levels were determined to be reduced, there was no significant change among the groups. Serum urea levels in both groups were higher than controls. Based on our results, it is possible to postulate that exogenous NIT can act as antioxidant against Cd toxicity and lipid peroxidation.
Keywords: cadmium; metallothionein; GSH-Px; MDA